Адаптація макромоделей електротехнічних систем та їхніх складових до програмних засобів моделювання перехідних процесів - Стахів, П.Г.; Гоголюк, О.П. (Технічна електродинаміка, 2012)
Analysis of the existing software tools intended for mathematical modelling of electric power system transient processes and difficulties that arise during their application are analyzed. A generalized alternative procedure to create separate macromodels of the electric power system elements and their groups using the universal algorithm of their identification and approaches to adapt them to the available software of mathematical modelling of transient processes are considered.